The social determinants and starting and sustaining quit attempts in a national sample of Aboriginal and Torres Strait Islander smokers - David P. Thomas; Kathryn S. Panaretto; Maureen Davey; Viki Briggs; Ron Borland (Australian and New Zealand Journal of Public Health, 2017)
Abstract Objective: To assess whether social, economic and demographic measures are associated with initiating and sustaining quit attempts in a national sample of Aboriginal and Torres Strait Islander smokers. Methods: We analysed data from 759 adults who reported smoking at least weekly in the Talking About The Smokes baseline survey (April 2012 – October 2013) and completed a follow up survey a year later (August 2013 – August 2014). Results: Almost none of the standard baseline socioeconomic indicators predicted making or sustaining quit attempts. However, becoming employed was associated with making quit attempts (OR 1.88) and both becoming employed (OR 3.03) and moving to purchase a home (OR 2.34) were both positively associated with sustaining abstinence of one month or more. More smokers who had insufficient money for food or essentials because of money spent on cigarettes had made a quit attempt (OR 1.47) and sustained abstinence of one month or more (OR 1.74). Conclusions and implications: Disadvantage does not seem to have pervasive negative effects on quitting. We should be more optimistic in our tobacco control activities with the most disadvantaged among Aboriginal and Torres Strait Islander smokers. Increasing personal empowerment (e.g. getting a job) may lead to at least short‐term improvements in quitting.